2018
DOI: 10.1029/2018pa003389
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Uncertainty in Sr/Ca‐Based Estimates of SST From the Coral Orbicella faveolata

Abstract: The strontium to calcium ratio (Sr/Ca) in aragonitic skeletons of massive corals provides a proxy for sea surface temperature (SST) that can be used to reconstruct paleoclimates across decades, centuries, and, potentially, millennia. Determining the reproducibility of Sr/Ca records among contemporaneous coral colonies from the same region is critical to quantifying uncertainties associated with the Sr/Ca‐SST proxy. We evaluated both intracolony and intercolony variability in Sr/Ca using five modern colonies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 66 publications
(135 reference statements)
4
35
0
Order By: Relevance
“…To date, Sr/Ca has been the most widely used coral paleothermometer (Figure 6b and supporting information Table S1; Bagnato et al, 2004;Calvo et al, 2007;Corrège et al, 2000;Fallon et al, 1999Fallon et al, , 2003Flannery et al, 2018;Gagan et al, 1998;Heiss et al, 1997;Hennekam et al, 2018;Jimenez et al, 2018;Kawakubo et al, 2017;Linsley et al, 2000;Marshall & McCulloch, 2001;McCulloch, 1999;Mitsuguchi et al, 1996;Nurhati et al, 2009;Ramos et al, 2017;von Reumont et al, 2018;Shen et al, 1996;Sinclair et al, 1998;Watanabe et al, 2017;Wu et al, 2013Wu et al, , 2014Zinke et al, 2004). However, separating the effects of temperature from the influence of vital effects on Sr/Ca has long proven difficult (Alibert & McCulloch, 1997;Corrège, 2006;de Villiers et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To date, Sr/Ca has been the most widely used coral paleothermometer (Figure 6b and supporting information Table S1; Bagnato et al, 2004;Calvo et al, 2007;Corrège et al, 2000;Fallon et al, 1999Fallon et al, , 2003Flannery et al, 2018;Gagan et al, 1998;Heiss et al, 1997;Hennekam et al, 2018;Jimenez et al, 2018;Kawakubo et al, 2017;Linsley et al, 2000;Marshall & McCulloch, 2001;McCulloch, 1999;Mitsuguchi et al, 1996;Nurhati et al, 2009;Ramos et al, 2017;von Reumont et al, 2018;Shen et al, 1996;Sinclair et al, 1998;Watanabe et al, 2017;Wu et al, 2013Wu et al, , 2014Zinke et al, 2004). However, separating the effects of temperature from the influence of vital effects on Sr/Ca has long proven difficult (Alibert & McCulloch, 1997;Corrège, 2006;de Villiers et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Muted levels of coral mortality elsewhere, including only 13 % mortality in the Gulf of Chiriquí, were correlated with the presence of thermally resistant zooxanthellae in the corals Baker et al, 2004; see also D' Croz and Maté, 2004). Collateral effects following the 1982-1983 event, particularly enhanced predation by Acanthaster (in the Gulf of Chiriquí) and increased bioerosion by sea urchins, were also far less severe after the 1997-1998 ENSO, due to precipitous declines of both taxa (Eakin, 2001;; see also Fong and Glynn, 2001). The effects of the 2015-2016 El Niño event were also minimal in Pacific Panama.…”
Section: Response To Enso Eventsmentioning
confidence: 95%
“…Reef frameworks and the coral skeletons that constitute them preserve well in the fossil and subfossil record, providing a historical record of the response of coral reefs to climate change (Jackson, 1992). Moreover, many of the perturbations listed above leave geochemical and taphonomic traces that can be used as proxies to reconstruct changes in environmental conditions (e.g., Cobb et al, 2013;Toth et al, 2012Toth et al, , 2015aFlannery et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in instrumentation, methodologies, cleaning techniques, and interlaboratory calibration (particularly for trace elemental proxies, e.g., Fernandez et al, 2011;Hathorne, Gagnon, et al, 2013;Nagtegaal et al, 2012;Schrag, 1999) have greatly improved precision while reducing the time and cost associated with record development. Fortunately, with increased replication of the Sr/Ca and δ 18 O paleothermometers, several studies have demonstrated that two records from the same location are typically sufficient to constrain chronological and other among-colony uncertainties (with limited return on investment for further replication, e.g., DeLong et al, 2007DeLong et al, , 2013DeLong et al, , 2016Flannery et al, 2017Flannery et al, , 2018. Nevertheless, additional replication may be beneficial where suboptimal transect qualities are present (e.g., DeLong et al, 2013;Reed et al, 2021).…”
Section: Replication and Reproducibilitymentioning
confidence: 99%
“…However, these new paleothermometers have uncertainties and limitations (e.g., Sr–U is limited to annual resolution), and these uncertainties have yet to be well constrained with replicated, long reconstructions across species and sites. On the other hand, a growing number of studies have demonstrated reproducibility of δ 18 O, Sr/Ca, and luminescence across colonies, sites, and even different species and methods (e.g., Allison & Finch, 2009; Cobb, Charles, Cheng, & Edwards, 2003; Cobb, Charles, Cheng, Kastner, & Edwards, 2003; DeLong et al, 2011, 2016; D'Olivo et al, 2018; Grothe et al, 2020; Grove et al, 2012; Grove, Kasper, et al, 2013; Grove, Zinke, et al, 2013; Hendy, 2002; Jimenez et al, 2018; Linsley et al, 2004; Rodriguez‐Ramirez et al, 2014; Stephans, 2004), reproducibility which can be further constrained with crossdating approaches and optimal sampling methods (DeLong et al, 2013, 2014; Flannery et al, 2018; Grothe et al, 2020; Sayani et al, 2019). Nevertheless, this debate has motivated studies on the incorporation of geochemical proxies into the coral skeleton during the calcification process.…”
Section: Constraining Uncertainties and Improving Interpretationmentioning
confidence: 99%